Exploring the Effect of Different Scanning Protocols on the Modulation Transfer Function - Arjah, H.; Osman, N. D.; ALMasri, H.; Anam, C.; Aziz, M. E. (Atom Indonesia, 2025)
The Iterative Reconstruction (IR) algorithm can enhance image quality and reduce patient dose. This study aims to evaluate the in-plane resolution (X- and Y-), in association with different IR and filtered back projection (FBP), on three different Computed Tomography (CT) scanners: General Electric (GE), Philips, and Siemens. Uniform water phantoms were scanned using 35 milligrays (mGy) and 65 (mGy and then reconstructed using 2- and 5-millimetre (mm) slice thicknesses. Images were reconstructed using the iterative Beam Hardening Correction (iBHC), Sinogram-Affirmed Iterative Reconstruction (SAFIRE), 4th generation hybrid statistical iterative reconstruction proposed by philips (iDose4), Filtered Back Projection (FBP), Adaptive Statistical iterative Reconstruction (ASiR-V), Weighted Filtered Back Projection (WFBP), Best Contrast or Brain Contrast algorithm (BC). All images were analysed using IndoQCT software. Automated Modulation Transfer Function (MTF) measurement was used to describe in-plane resolution. From the Siemens CT scanner findings, MTF at 10 % (MTF10) was increased by applying the iBHC algorithm from 0.52 to 0.57, but MTF10 of SAFIRE and WFBP showed no difference. For the Philips CT scanner, the iDose4 technique did not affect MTF10 compared to FBP, while the post-processing by BC decreases MTF10 from 0.5 to 0.49. For the GE CT scanner, the MTF is affected by radiation dose, while the ASiR-V MTF curve had no difference compared to FBP, with the highest MTF10 value of 0.67 for 35 mGy protocol compared to 0.64 for 65 mGy protocol. The image resolution is affected by CT dose and the use of reconstruction algorithms. These associated parameters may enhance or reduce image resolution.